A Narrative Review about Prosocial and Antisocial Behavior in Childhood: The Relationship with Shame and Moral Development - Susanna Maggi; Valerio Zaccaria; Maria Breda; Maria Romani; Franca Aceti; Nicoletta Giacchetti; Ignazio Ardizzone; Carla Sogos (MDPI AG, 2022)
We conducted a literature review aimed at identifying the origins of shame as well as its effects on moral development, especially in terms of behavioral outcomes, and we reflected on the practical implications of our findings. We explored the role of shame in moral development through cultural differences and parental influences, collecting evidence of psychopathological consequences of primary moral emotion dysregulation. These studies showed a dichotomous feature of shame, as a prosocial behavior enhancer in morally relevant situations and, simultaneously, a risk factor for aggressive and antisocial behaviors on other occasions. Dysregulated shame leads to maladaptive interpersonal behaviors, which could evolve towards psychopathological paths. Therefore, an integrated intervention is recommended in children with emotional/behavioral problems.